Answer:
x = 1 and y = −2
Explanation:
Rewrite equations:
x + 2y = −3
3x − 2y = 7
Step 1: Solve x+2y=−3 for x:
x + 2y = −3
x + 2y + −2y = −3 + −2y (Add -2y to both sides)
x = −2y − 3
Step 2: Substitute −2y − 3 for x in 3x − 2y = 7:
3x − 2y = 7
3(−2y − 3) − 2y = 7
−8y − 9 = 7 (Simplify both sides of the equation)
−8y − 9 + 9 = 7 + 9 (Add 9 to both sides)
−8y = 16
−8y/−8 = 16/−8 (Divide both sides by -8)
y = −2
Step 3: Substitute −2 for y in x = −2y − 3:
x = −2y − 3
x = (−2)(−2) − 3
x = 1 (Simplify both sides of the equation)